The Extent to Which Social Validity Criteria are Met in the Individual Educational Plans of Students with Autism Spectrum Disorder in the City of Jeddah - Alharty, Bashaer Meshal; Maajeeny, Hassan Osama (Journal of Educational and Psychological Sciences, 2023)
The purpose of this study was to determine the social validity of some goals of students with autism spectrum disorder in Jeddah. To accomplish this, the study used the descriptive survey method and created a questionnaire to investigate the social validity of some goals in individual educational plans, then administered to a random sample of community members. The sample consisted of 291 parents of students with autism who attended governmental and private centers and schools in Jeddah. The study concluded with a set of results, the most notable of which was the availability of social validity criteria in some of the goals of students' plans with autism spectrum disorder in Jeddah. The goal of developing creative skills such as drawing, sculpture, and carving and working with them as a profession and career comes first as the highest standard of social validity. The goal of developing musical skills, such as playing an instrument, singing, and working with music as a profession, had the lowest level of social validity. Furthermore, parents of younger students (5- 0) were more accepting of the goals, and the parents' financial status had no influence on their choices. The (illiterate) mothers were also more accepting of the goals. Based on the findings, the current study suggests developing standardized tests to assess the suitability of goals based on social validity in addition to additional investigative research efforts to explore the validity of the goals within students’ individualized plans.
Keywords: social validity; Autism Spectrum Disorder; Individual Educational Plans